ChemInform Abstract: The Impact of Structural Relaxation on Spin Polarization and Magnetization Reversal of Individual Nanostructures Studied by Spin‐polarized Scanning Tunneling Microscopy. Issue 48 (2nd December 2014) - Sander, Dirk; Phark, Soo‐Hyon; Corbetta, Marco; Fischer, Jeison A.; Oka, Hirofumi; Kirschner, Juergen
Abstract Review: [102 refs.]